New phytochemical based cocktail for in vitro adipocytes differentiation - Abdul Majid, Fadzilah Adibah; M., Taher; Sarmidi, Mohd. Roji (Unknown, 2005)

(untitled)
Adipocyte (fat tissue) is commonly used in in vitro study of diabetes and many other areas in endocrinology. Prior to testing, preadipocytes (fat cells) culture will be differentiated to adipocytes using a mixture of three compounds, which are insulin, dexamethasone and isobutylmethylxanthine. The cocktail of these components is expensive. Furthermore, dexamethasone has been recently categorized as a restricted item in Malaysia. Therefore, in this work, an alternative component to replace these compounds is necessary. The first scope of the study is to replace insulin with suitable phytochemical based compound using Malaysian rich biodiversity. Based on the lead compound screening of phytochemicals for diabetes, cinnamon water extract has shown to have the ability to increase glucose uptake in adipocytes culture tested. The active component in the extract has been identified as Cinnamtannin B1 and the results indicates that this compound react similar to insulin in promoting preadipocytes differentiation to adipocytes tissue. First scope of the project has been achieved where Cinnamtannin B1 is found to be a potential candidate to replace insulin in currently used adipocytes differentiation cocktail. This finding is hoped to offer the possibility of using a non biological alternative to insulin in adipocytes differentiation.